Genesıs, Ecosystems And Prıncıples - Peñaranda Galvis, Vidal Fernando, Rodríguez Miranda, Juan Pablo, Gómez Aguilar, Dora Luz (International Journal of Advanced Science and Technology, 2020)
The strength of being is in the ability to build new ways of life to live with their peers. Wherever he stops, his spirit must inhabit the whole environment with pleasure, the signs will be the open meeting of temperance that reduces distances. Under each roof, the coexistence will be marked, and there will always be the expectation of the farewell, latent in watching over the wait and march of the happy encounter in the return. Weakness and sadness should have no place. Adherence and severity are feelings that respond to internal control, without pretending indifference work to the extent that thinking seeks to replace sadness by the exogenous approach. Clusters cross paths, likely of bright people or intruders. In the supposed, of mixed feelings, glory or lie and/or truth depending on each thought, design and destination, the external forces have their own script. A true guide in life is the effort to contribute to a culture of peace, with the intuitive assumption that the kindly strength with the meanings of community and bio-ecology will always be blessed, according to spiritual forces of generosity and gratitude.